Food waste composting in cafeterias: a case study - Saifullizan, Muhammad Irfan Syafri; Jumat, Erna Mariana; Dang, Elvida Runai; Ithnain, Nurnabila; Ab. Aziz, Siti Hanisah; Radin Mahamed, Radin Maya Saphira; Al-Gheethi, Adel (Penerbit UTHM, 2020)
Excessive waste has become the environmental issue that cannot be neglected. Food wastes are among the waste that filled up the landfill sites and they are abundance. The impacts of massive mountains of food waste in the landfills affect the local community surrounding the area. They do not only cause unattractive sight but also produce bad odour and gas such as methane gas. This gas is dangerous than any greenhouse gasses because it can easily explode. Another problem is leachate, which can affect the clean ground water. Thus, this project proposes a conventional method to reduce the food waste by composting. The proposed approach is made because the compost materials will breakdown and can be used as fertilizer for gardening. As the project reached the end, it is found that composting is a very effective way to reduce food waste and it gives more benefits.